Psycho-Correction Means in the Process of the Moral Development of a Pupil - Osik, O. V. (Psychological Prospects Journal, 2012)
Psycho-correction means in the process of the moral development of a pupil are considered in the article. The classification of the psychocorrection means in accordance with the tendency, content, form is given as well as the conditions of the individual psycho-correction, methods of the individual psychocorrection influence. Certain specific features of the correction process and the principles of composing the psycho-correction programmes are outlined. Some leading mechanisms of the correction influence are characterized, namely: to communicate the information; to cast on the hope; the all-roundness of sufferings, feelings and awareness by the pupil of the fact that he is not аlone in the world; altruism; correctional recapitulations of the initial family group; the development of the technique of the interpersonal communication; imitational behavior; interpersonal influence; group unity; catharsis; corrective emotional experience; confrontation; training.
Keywords: psycho-correction means classification process influence mechanism method programme moral development pupil